Cuddapah - Brackenbury, C. F. (Maven Books, New Delhi, 2022)
C.F. Brackenbury's "Cuddapah," reissued by Forgotten Books, offers a valuable historical snapshot of the Cuddapah district, now Kadapa. This 2023 hardcover is not a mere revision of J.D.B. Gribble's 1875 manual, but a distinct gazetteer, reflecting evolving approaches to documenting regional information. Brackenbury's work, compiled amidst his own district resettlement duties, relies heavily on contributions from numerous officials and individuals, highlighting the collaborative nature of its creation. While modern readers may find the separation of statistics into appendices somewhat cumbersome, the book's strength lies in its preservation of historical context and detail. Forgotten Books' commitment to digitally reconstructing and preserving such works ensures that this important piece of regional history remains accessible. Imperfections, where present, are intentionally left to maintain the authenticity of the aged original, making it a fascinating artifact for both historians and those interested in the region's past.
Includes index.
Keywords: Cuddapah district history / Gazetteer; Regional manuals (India).; Historical statistics (India).; Colonial administration (India).; Forgotten books publishing / historical reproduction